O desenvolvimento humano como direito e objetivo educacional no currículo da educação infantil - Medeiros, Cássia Maria Lopes Dias (Universidade do Vale do Rio dos Sinos, 2021)
The concern with human development is currently on the agenda in several fields of studies and research. In the educational field, this aspect became a central one, notably in Primary Education, in which the full development of children and adolescents became its great purpose. Nowadays, this aspect receives more and more attention, especially in the Early Childhood Education stage, where the understanding that educational investments, at this stage of life, are fundamental for human development, is consolidated. Developing fully (or wholly) children through school education has been the primary objective of early childhood schools. It is worth noting, therefore, that this research, by focusing on this stage of education, understands that this field has been constituted in a space of many clashes that fall within the area of Curricular Studies and childhood. In this work, it was proposed to carry out an analysis of the current Curricular Policy document (BNCC – EI, version 2017), observing the regularities about the meaning that is attributed to human development and that can lead to the construction of curricular proposals today. In this way, two categories were formulated in a more specific way that constituted the documentary analysis: (a) human development as an educational right; and (b) human development as a curricular objective. It should be said that, even if it declared itself relevant and stated its commitment to equity, which was fully contemplated in the document, it was observed that the BNCC ended up not addressing, directly, issues related to the specificities that go through the experiences of each child. Therefore, it was found that human development, even understood as an educational right and a curricular objective, is still imprisoned in an organic and linear perspective, quite common in traditional models of education. This finding provides that the development of curricula for Early Childhood Education can be directed to only one type of child: those who were able to develop as expected. To conclude, the following question is asked: In this way, is full development for everyone? The concept of democracy as an analytical tool in this discussion – inspired by the writings of John Dewey – was used in order to bring relevant discussions to the topic that may assist in the construction of more democratic curricula in the schooling process of Brazilian childhood.
Keywords: Currículo; Desenvolvimento humano; Educação Infantil; BNCC; Curriculum; Human development; Child education; ACCNPQ::Ciências Humanas::Educação